Estimation of Carbon Flux Through Litter Fall in Forest Plantations of India - Raizada, A.; Parandiyal, A. K.; Ghosh, B. N. (Indian Forester, 2003)
The paper deals with the estimation of C flux through litterfall (total and leaf litterfall alone) in forest plantations of India, occurring in four major forest groups of India. Using published studies covering 82 stands and 24 species raised as plantations, the annual C flux rates were computed. The C flux rates (M t C/yr) from total litter were 2.17, 1.18, 1.60 and 2.30 in tropical moist deciduous forests, tropical dry deciduous forests, montane sub-tropical forests and montane temperate forests, respectively. The C flux rates from leaf litter alone were highest (3.03 M t C/year) in montane sub-tropical forests. Results indicate that plantations of short rotation tree species with regular leaf shedding patterns have more C sequestering capacity than species with unimodal or bimodal leaf shedding patterns. Such species could be raised in wastelands for twin purposes - biomass production and carbon sequestering.